ADEC dan Group Investigation dalam Meningkatkan Berpikir Kritis Siswa - Mariani, Siti Salmiyatun; Waluyo, Edy; Ahyan, Shahibul (JOEAI (Journal of Education and Instruction), 2025)
This study aims to examine the effect of the RADEC and Group Investigation learning models on students' critical thinking skills, as assessed by their level of learning motivation (high and low). The research method used was a quasi-experimental study with a 2x2 treatment-by-level analysis and two-way ANOVA analysis. This study involved eighth-grade students at SMP Islam Hidayatuttauhid Esot. The results showed that learning motivation had no significant effect on the effectiveness of both models for highly motivated students. Low-motivated students were unable to fully capitalize on the advantages of both learning models, highlighting the importance of motivational interventions in improving learning outcomes. The conclusion is that the Group Investigation learning model is more effective in enhancing students' critical thinking skills than the RADEC model. The practical implication of these findings is that teachers should focus on increasing student motivation through differentiation strategies and social support to maximize the potential of these learning models.   Keywords: Group Investigation, Critical Thinking Skills, Learning Model, Learning Motivation, RADEC